Clinical Nurse Specialist and Clinical Nurse Leader Dyad: A Model Promoting Clinical Resilience During COVID-19 and Beyond. Issue 3 (May 2022) - Racelis, Mary Carol; Hallberg, Elizabeth; Filer, Rachel; Gross, Megan; Brownlee, Camille; Stifter, Janet; Losurdo, Holly; Cook, Heather
Abstract : Purpose/Objectives: This article describes an innovative clinical nurse specialist (CNS) and clinical nurse leader (CNL) dyad partnership model. Complexity science framework and clinical exemplars demonstrate how the CNS and CNL roles function synergistically to stabilize complex patient care. Description of the Project/Program: In spring of 2020, the COVID-19 crisis presented an immediate opportunity to leverage the increased demand for clinical change by leading, designing, and capturing the value of CNS-CNL dyad to achieve goals. Outcome: The exemplars outline how the partnership promoted translation of knowledge to care for 21 new patient populations and created training for the complex respiratory management during the 6-month project. Rapid response utilization increased from an average of 5 to 10 per month. There was no change in the number of code blue activations on the unit. The third exemplar promoted personal protective equipment clarity and attention to nurse safety. Twelve percent of total staff (n = 104) were diagnosed with COVID-19. Staffing remained stable with 1% resignations (n = 3). Conclusion: The CNS-CNL dyad revealed an infrastructure built to withstand forces of institutional change. The clinical exemplars provide details for leaders to understand how these separate roles partner to translate knowledge and skills and sustain complex change to meet quality goals.